Recombination coefficient analysis of hydrogen plasma species in the afterglow regime - Felix Boy Martupa Sihombing; Saktioto Saktioto; Kusherbayeva Maikul; Kushkimbayeva Bibara (Science, Technology, and Communication Journal, 2026)
The recombination coefficient of hydrogen plasma using the six thermal hydrogen species in the afterglow condition was analyzed through MATLAB computational modeling to determine the logarithmic density, and then to determine the difference between conduction and convection. This study aims to model the dynamics of recombination and determine the recombination coefficients of hydrogen species against temperature variations. This modeling was carried out using zero-dimensional chemical kinetic equations derived from the continuity equation, namely the reaction rate calculated using modified Arrhenius. This modeling is integrated numerically using the Runge-Kutta method. The density results of hydrogen species show a consistent decrease in temperature variation related to the ideal gas law, but the recombination coefficient increases with increasing temperature. This upward trend indicates that there is a dominance of three-body recombination processes over atmospheric pressure and afterglow conditions.